Economic Ethics as a Gospel Priority in the Pastoral Ministry of Jonathan Edwards - Forster, Greg (Jonathan Edwards studies, 2019)
Jonathan Edwards made economic ethics - including generosity, witness against greed, justice for the oppressed and economic development - a vital concern at key points of his pastoral ministry, because he saw these things as necessarily connected to the proclamation of the gospel of salvation in Christ. Historical memory tends to neglect this aspect of his story, but concerns about economic ethics played a pivotal role in Edwards' conduct. This article reviews existing scholarship on Edwards' public theology, noting the paucity of attention to his view of economic ethics but the important insights that have been generated into his social ethics more generally. It then reviews three of the most important periods of Edwards' pastoral career - the revival in Northampton connected to the Great Awakening, the emergence of conflict between Edwards and other leaders in his church, and his service in the mission to the native population in Stockbridge - to show how, in each case, Edwards was required to decide what concerns he would prioritize as a pastor, and in each case economic ethics emerged as one of the priorities for which he was most willing to take risks and make sacrifices. We would benefit from a fresh encounter with Edwards' confidence that the gospel and economic life cannot be separated, and his courage in living out that connection in a costly way in his pastoral ministry.